Management of the Formation of Rating Preferences of Economic Entities upon Collective Choice - Motorygin, Yury D.; Artamonov, Vladimir S.; Maximov, Alexander V.; Trofimets, Elena N.; Trofimets, Valeriy Y. (International Journal of Economics and Financial Issues, 2017)
The applicability of a set of methods in the case of obtaining mixed results of the final ranking of economic entities in the process of their rating assessment has been substantiated. A new method of the formation of rating preferences upon collective choice has been proposed. The methodology is based on the following: an information base in the form of a summary table of ratings of compared entities; a procedure for the formation of rating preferences based on a rank-sum (or arithmetic means of ranks); a procedure for the formation of rating preferences with the joint application of rating arithmetic means and position indicators; a procedure for the formation of rating preferences using the Kemeny median. The proposals for the calculation of weighting factors of the voting procedures and modification of the procedure for profiling the preferences using the Kemeny median have been made. An algorithm for the use of the proposed method has been developed. Methodology testing has been conducted upon the rating assessment of the financial and economic condition of industrial enterprises. Keywords: system analysis, management of economic systems, economic-mathematical modeling, rating assessment, financial and economic condition JEL Classifications: P40, P49